Jamet Stereotyping in Jedag-Jedug Music: An Analysis of Jedag-Jedug Music Stereotype - Tiantini, Wendy Belinda; Khusyairi, Johny Alfian; Afdholy, Nadya; Puspita, Yulia Mega (Jurnal Seni Musik, 2023)
Several music genres have stereotypes from the society, especially music that comes from low culture. One of the types of music that is stereotyped is jedag-jedug music, a music that is identical with fast beats and specific video editing. This type of music is widely known due to the influence of the TikTok application, which is a social media platform that offers audio-visual content. Jedag-Jedug music is often stereotyped as jamet music and also considered as tacky or alay. This research aims to find out how jamet stereotypes in Jedag-Jedug music can change and become a popular trend on social media. The approach used in this research is a qualitative approach using in-depth interviews with participants. The criteria for participants were participants aged 18 years and over and who had listened to jedag-jedug music with various economic and educational backgrounds. Primary data in this research are interview transcripts and secondary data used are journal articles, books and other supporting sources. To analyze the data, researchers used Dual-Process by Shelly Chaiken. There are three aspects that form a stereotype which are cognitive, affective, and behavioral aspects that will be used to see how stereotypes are changed in the jedag-jedug music. The result found in this study was that participants experienced a change in their views towards the stereotypes that exist in jedag-jedug music. The shifting of the stereotypes occurred because of the popularization of jedag-jedug music in social media which influence the participants’ cognitive, affective, and behavior.